Pengalaman Keluarga Dalam Merawat Pasien Skizofrenia Tak Terorganisir Di Rumah Sakit Jiwa Daerah Surakarta - Dewi, Emi Putri; , Arum Pratiwi, S.Kp.,M.Kes; , Enita Dewi , S.Kep.,Ns.,M.N (2016)
Disorganized schizophrenia is a type of mental disorder whose symptoms are characterized by the presence of a strange attitude and chaotic behavior, as well as the flat affect and impaired association. Therefore, it takes a caregiver to care for and meet the needs of patient with schizophrenia, as well as the elements of the family as primary caregiver is very influence the healing of patients with schizophrenia.The purpose of this study was to know in depth of experience of the family in caring for patient with disorganized schizophrenia. This study is a qualitative study using interpretative approach phenomenology analysis (IPA).Respondents in this study were 6 people.Sampling technique used was purposive sampling technique.The procedures of collecting data in this study were using the technique of in-depth interviews, observation and recording.Data analysis used was interpretative phenomenology analysis (IPA).Results of this study resulted in ten major themes.The first theme was the prodromal phase in schizophrenic patients.The second theme was the positive symptoms in schizophrenia.The third theme was carrying out the duties of family health to family members who suffered from schizophrenia, which consists of four sub-themes, namely taking a decision on the medication, caring for family members with disorganization schizophrenia, modifying the environment, and utilize health services.The fourth theme was the physiological response of the family as a caregiver.The fifth theme was psychological response of family as a caregiver that consists of two sub-themes, namely the psychological response of the family in the early time of patient was diagnosed with schizophrenia, and the psychological response of the family in caring for sick family members.The sixth theme was social stigma.The seventh theme was spiritual response. The eighth theme was financial factor.The ninth theme was family coping during cared for.The tenth theme was the expectation the family.